PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 103 PEKANBARU - Liza Lestari; Mahmud Alpusari; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research by low learning outcomes IPS. Causes of low student learning outcomes are caused not exactly learning model used in teaching social studies teacher teaching method is verbal and does not involve students in learning. This research aims to improve IPS learning outcomes in the fifth grade students of SDN 103 Pekanbaru through Jigsaw cooperative learning. The research was conducted in the second semester of the academic year 2014/2015 in SDN 103 Pekanbaru. Design research is classroom action research. This research was conducted in two cycles. Research procedures conducted in the class action are planning, implementation, observation and reflection. The subjects were students of class V SDN 103 Pekanbaru. Data and instruments used in the form of learning tools and a data collection instrument, namely the observation sheet and test questions (UH). Data collection techniques using observation techniques and test techniques. The data analyzed in this study data on the observation of teacher activity, student activities, and student learning outcomes data. The results showed after application of jigsaw cooperative learning increased student participation in the classroom. Activities of students and teachers has increased every meeting, in accordance with the lesson plan that has been designed. Resulting in increased student learning outcomes in social studies class V SD Negeri 103 Pekanbaru. In the first cycle obtained 20.25% increase in learning outcomes and the second cycle 31,50%. Based on these results, we can conclude the application of jigsaw cooperative learning model can improve student learning outcomes in social studies learning.Keywords: Jigsaw Cooperative Learning , IPS Learning Outcomes